ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH PERIODE 2018-2020 - Firda Fikra Tania; M. Cholid Mawardi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to compare the financial performance produced by Conventional Banks and Islamic Banks based on financial ratios during the 2018-2020 period. This research is a type of quantitative research. The population in this study are conventional banks and Islamic banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period, totaling 51 banks. The sample in this study amounted to 30 banks, 20 conventional banks and 10 Islamic banks were taken using purposive sampling technique. The data collection method uses the documentation method by collecting data from the IDX website and then reading the contents of the financial statements. This study uses financial ratios including Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return On Equity (ROE), Non-Perfoarming Loan (NPL), and Operating Cost of Operating Income (BOPO). This study uses the Independent Sample t-Test hypothesis test. The results showed that there were no significant differences between conventional banks and Islamic banks in the ratio of CAR, LDR, ROE, NPL, and BOPO.Key Words : Capital Adequacy Ratio, Financial Performance, Loan to Deposit Ratio, Non Performing Loan, and Return On Equity